COMPARATIVE ANALYSIS OF MANUFACTURER VS. RETAILER REFURBISHING MODELS: PROFITABILITY, PRODUCTION EFFICIENCY, AND STRATEGIC IMPLICATIONS - Sudibyo, Nugroho Arif; Farida, Anisatul; Kurdhi, Nughthoh Arfawi (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
This paper explores the profitability and operational efficiency of refurbishing models managed by manufacturers versus retailers, focusing on equilibrium pricing, production quantities, and profit outcomes in each scenario. It reveals that the retailer refurbishing model often leads to higher production quantities and greater profitability for manufacturers, particularly when refurbishing costs are significant or when manufacturers do not achieve notable efficiency gains through intelligent manufacturing. In contrast, the manufacturer refurbishing model may be less advantageous when these conditions are unfavorable. The findings underscore the need for manufacturers to carefully assess refurbishing costs, potential efficiency improvements, and market dynamics before selecting a refurbishing strategy. This study provides practical insights for optimizing refurbishing decisions and contributes to the broader understanding of supply chain management. Additionally, it sets the foundation for future research on how emerging technologies and market trends may influence the effectiveness of different refurbishing models.